Production of hyperimmune serum against genotype VII Newcastle disease virus in rabbits with several applications (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: This study aimed to produce hyperimmune serum against genotype VII Newcastle disease virus (NDV) with several applications. Materials and Methods: Production of hyperimmune serum against genotype VII NDV was performed on eight New Zealand white rabbits divided into four groups. Rabbits were immunized three times on the 1st day, the 14th day, and the 30th day. Blood sampling was carried out on the 8th day after the third immunization. Results: All groups showed the same pattern of hemagglutination inhibition (HI) titer results. HI titers would peak on the 5th or the 9th day after the second immunization, then decrease until the 3rd day after the third immunization, and increase again on the 5th day after the third immunization. Rabbits immunized intravenously showed higher HI titers than the other groups. These results indicate that the intravenous route for hyperimmune serum production against genotype VII Newcastle disease virus greatly affects the immune response result. Conclusions: The production of hyperimmune serum by intravenous immunization three times was able to produce the highest titer of 210 at 38 days. The agar gel precipitation test and the Western blot assay showed that the hyperimmune serum was specific for the Newcastle disease antigen.J. Adv. Vet. Anim. Res., 9(2): 211–220, June 2022http://doi.org/10.5455/javar.2022.i586